Reverend R. J. Henle, S. J. Saint Thomas and Platonism, A study of the Plato and Platonici texts in the writings of Saint Thomas.- The Hague. Martinus Nijhoff, 1956 - Benavides, Alberto (Estudios de Filosofía, 1975)
No presenta resumen.